Study of rural women's decision-making abilities and their participation in employment generation programs using surveys (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Rural women’s empowerment has emerged as a critical focus area in India’s development agenda, particularly in enhancing their autonomy in decision-making and participation in employment generation programs. Despite numerous government and non-government efforts, rural women still face significant barriers in asserting agency over their personal and economic lives. This study investigates rural women's decision-making autonomy and their participation in employment generation programs across three socio-economically comparable districts. Utilizing a descriptive cross-sectional survey of 300 respondents, the research explores the extent of autonomy women exercise in household, financial, and social decisions, and how this autonomy influences their engagement in government and NGO-led employment initiatives. Findings indicate that while a majority of women share joint decision-making power in household and social matters, financial autonomy remains limited, with only 29% of respondents exercising full control over economic decisions. Participation in programs like MGNREGA is relatively high, yet awareness and involvement in NGO-driven skill development programs are significantly lower. A strong positive correlation was found between higher levels of autonomy and active participation in employment schemes 67% of women with high decision-making autonomy were active participants compared to only 18% with low autonomy. The study underscores the need for multi-dimensional policy interventions aimed at enhancing rural women's empowerment for inclusive and sustainable development. .